Effiency gains from the elimination of global restrictions on labour mobility: An analysis using a multiregional CGE model - Ana María Iregui (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper computes the worldwide efficiency gains from the elimination of global restrictions on labour mobility using a multiregional CGE model. A distinctive feature of our analysis is the introduction of a segmented labour market, as two types of labour are considered: skilled and unskilled. According to our results, the elimination of global restrictions on the mobility of skilled and unskilled labour generates worldwide efficiency gains that could be of considerable magnitude. When only skilled labour migrates, the worldwide efficiency gains are smaller, as this type of labour represents a small fraction of the labour force in developing regions. – migration ; applied CGE modelling ; labour market segmentation
Keywords: C68; F22; R13; R23; 330; Arbeitsmobilität; Arbeitsmarktsegmentierung; Allgemeines Gleichgewicht; CGE-Modelling